2021
DOI: 10.3390/cancers13246257
|View full text |Cite
|
Sign up to set email alerts
|

miR-335 Restrains the Aggressive Phenotypes of Ovarian Cancer Cells by Inhibiting COL11A1

Abstract: High collagen type XI alpha 1 (COL11A1) levels are associated with tumor progression, chemoresistance, and poor patient survival in several cancer types. MicroRNAs (miRNAs) are dysregulated in multiple cancers, including epithelial ovarian carcinoma (EOC); however, the regulation of COL11A1 by miRNAs in EOC remains unclear. We examined the role of miRNAs in regulating COL11A1 expression. We identified miR-509 and miR-335 as the candidate miRNAs through an online database search. EOC cell treatment with miR-335… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…It affects cancer progression by regulating several downstream genes involved in biological processes such as cell proliferation, apoptosis, metastasis, and signal transduction. [ 15 ] COL11A1 overexpression has been observed in many cancer types. [ 16 ] Studies have shown that COL11A1 is highly expressed in patients with gastric cancer, which may be a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…It affects cancer progression by regulating several downstream genes involved in biological processes such as cell proliferation, apoptosis, metastasis, and signal transduction. [ 15 ] COL11A1 overexpression has been observed in many cancer types. [ 16 ] Studies have shown that COL11A1 is highly expressed in patients with gastric cancer, which may be a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients with low miR335 levels were susceptible to advanced-stage cancer, poor response to chemotherapy, and early relapse. These findings highlighted the importance of miR-335 in downregulating COL11A1-mediated ovarian tumor progression, chemoresistance, and poor survival and suggested the potential application of miR-335 as a therapeutic target ( 37 ). Kang et al.…”
Section: Regulation Of Col11a1 In Human Cancermentioning
confidence: 92%
“…We ( 37 ) identified miR-335 as the candidate miRNAs that may regulate COL11A1 expression through an online database search. Further mechanistic experiments revealed that epithelial ovarian cancer (EOC) cell treatment with miR-335 results in phenotypes that mimic those induced by abrogated COL11A1 expression and suppresses cell proliferation and invasion, in addition to increasing the sensitivity of EOC cells to cisplatin.…”
Section: Regulation Of Col11a1 In Human Cancermentioning
confidence: 99%
“…It can assist chemotherapy agents in forming a pro-oxidant effect so that cancer cells increase and cell proliferation can be inhibited [3]. Flavonoids are one of the antioxidants that play a role in inhibiting cancer cells by binding to the death receptor (TNF-R) and Fas-associated Death Domain (FADD), which form the Death Inducing Signaling Complex (DISC) [17][18][19][20][21].…”
Section: Cytotoxic Activity Testmentioning
confidence: 99%